Brazil Developing Current Research Information Systems (BrCRIS) as data sources for studies of research - Luiz Pinto, Adilson; de Carvalho Segundo, Washington Luis R.; Dias, Thiago Magela Rodrigues; Vivian Santos Silva; Gomes, Josir Cardoso; Quoniam, Luc (Iberoamerican Journal of Science Measurement and Communication, 2022)
Objective. BrCris/IBICT is presented as a scientific and technological recommender system based on a collaborative information filter, enabling users to receive recommendations fitting their profile. The BrCris/IBICT is inspired by PTCRIS Project and LA Referencia and is designed to store, manage and exchange contextual metadata for research activity financed by Government Agencies. Therefore, it intends to present the BrCris/IBICT, which has as its central objective the construction and monitoring, through the interoperability of Brazilian science and technology data, in a single system, with capillary articles in specificities. Design/Methodology/Approach. The proposal and data modeling started in 2015 and matured as a handy tool in 2021. With semantic questions asked and all data finally certified, your recommendation systems proved to be an evolutionary process demonstrating the acquired know-how. The current research had an explanatory, descriptive approach for exploring, analyzing, and treating the data obtained in the tool in an explanatory way. Results/Discussion. As the main results, we can highlight that though the spectrum of recommendations is infinite, BrCris/IBICT presents four models to recommend relevant contents: scientific production, theses and dissertations; patents and innovation; and scientific editors. The future will prove how successful the interactions are, but the certifications will be continuous. Conclusions. BrCris, even though it is in the conclusion phase, already has an extensive consolidated dataset, representing consistent graphics on the dashboard, which may help the scientific community when it becomes publicly available.